(untitled) (Studia Prawnicze / The Legal Studies, 2001)
Przez określenie "spółka handlowa" należy rozumieć zarówno trwały stosunek prawny powstający na mocy umowy spółki handlowej określonego ustawowego typu, jak i jednostkę organizacyjną, tzn. prywatnoprawną organizację wspólników, w którą łączą się dla osiągnięcia wspólnego celu co najmniej dwie osoby - chyba że chodzi o jednoosobową spółkę kapitałową - i dla realizacji którego wnoszą do tworzonej spółki w formie wkładów (pieniężnych lub aportów) określone wartości majątkowe. Brak woli zawarcia umowy i zawiązania spółki prowadzi do pozorności umowy spółki i w konsekwencji uniemożliwia ważne zawarcie tej umowy. Nieważne jest bowiem oświadczenie woli złożone drugiej stronie za jej zgodą do pozoru - zob. art. 83 § 1 k.c. Nie jest również dopuszczalne zastępowanie aktów woli co do uczestnictwa określonych osób w jakiejś spółce decyzjami innych podmiotów, nie mających żadnych kompetencji do składania oświadczeń, które prawnie wiązałyby te określone (inne) osoby. Ze względu na ustawowe ograniczenie swobody czynności prawnych uczestników umowy spółki akcyjnej, a także walnego zgromadzenia spółki (zawarte w art. 304 § 3 k.s.h.), nie jest w ogóle dopuszczalna zmiana określonego w k.s.h. dolnego limitu składu rady nadzorczej spółki akcyjnej. "Zgodny zamiar stron" obejmuje swą treścią znaczeniową określony w umowie lub statucie spółki tzw. przedmiot działalności spółki (zob. np. art. 21 § 1 pkt 2, art. 25 pkt 2, art. 91 pkt 2, art. 105 pkt 2, art. 130 pkt 2, art. 157 § 1 pkt 2 i art. 304 § 1 pkt 2 k.s.h.). W związku z tym przewidziane w art. 3 k.s.h. "wniesienie wkładów" do spółki nie jest, rzecz jasna, celem, ale jedynie środkiem do osiągnięcia (realizacji) zakładanego przez wspólników (akcjonariuszy) ich wspólnego celu. Przepisy dotyczące umów poszczególnych ustawowych typów spółek handlowych w zasadzie nie zawierają regulacji określających bezpośrednio oznaczony obowiązek uczestnika spółki do dodatkowego współdziałania w sposób jeszcze inny niż wynikający z art. 3 k.s.h. Jednakże pośrednio obowiązek taki wynika z tych przepisów: a) w spółce jawnej, komandytowej i komandytowo-akcyjnej - w zakresie obowiązku wspólnika jawnego lub komplementariusza co do prowadzenia spraw spółki, chyba że in casu dany wspólnik został uwolniony od obowiązku prowadzenia tych spraw; b) w spółce partnerskiej - w zakresie wykonywania przez partnera swego (wolnego) zawodu w spółce; c) w spółce komandytowej - co do oznaczenia przez komandytariusza w tekście umowy określonego kwotowo zakresu odpowiedzialności wobec wierzycieli za zobowiązania spółki, czyli tzw. sumy komandytowej. Umowa lub statut spółki mogą nakładać na określonego uczestnika spółki inne jeszcze niż wniesienie wkładu obowiązki wobec spółki (zob. np. art. 159 lub 304 § 2 pkt 2 k.s.h. W takim wypadku obowiązek realizacji świadczeń, oznaczonych w ten sposób, wynika z treści dodatkowego zobowiązania umownego danego uczestnika spółki i wchodzi do zakresu obowiązku współdziałania tego uczestnika. Jego przedmiotem jest to szczegółowo oznaczone (w umowie lub statucie spółki) świadczenie na rzecz spółki. Jeżeli po zarejestrowaniu spółki kapitałowej okaże się, że w umowie spółki brak jest oznaczenia jej uczestników bądź też brak jest określenia objętych przez wspólników albo akcjonariuszy praw udziałowych, sąd rejestrowy, działając na podstawie art. 21 k.s.h., może wydać orzeczenie o rozwiązaniu wpisanej do rejestru spółki kapitałowej ze względu na to, iż "nie zawarto umowy spółki" - zob. art. 21 § 1 pkt 1 k.s.h. Jeżeli natomiast "umowa spółki nie zawiera postanowień dotyczących firmy, przedmiotu działalności spółki, kapitału zakładowego lub wkładów", sąd będzie mógł orzec o rozwiązaniu takiej spółki jedynie na podstawie art. 21 § 1 pkt 2 k.s.h. The terms ’commercial partnership’ and “commercial company” are to be construed as both a permanent legal relationship created by the articles of association of a commercial company of a certain statutory type and an organisational unit, i.e. a private-law organisation binding at least two partners or shareholders - unless it is a single-member ]company - in order to achieve a common goal, and for the realisation of which they contribute certain assets to the created company in the form of contributions (in cash or in kind). Unwillingness to conclude the partnership agreement or the articles of association and establish a partnership or a company renders the arrangement sham, thus preventing the valid establishment of the entity. This is because a declaration of intent made to the other party with his or her consent to the appearance is invalid - cf. Article 83 § 1 of the Civil Code. It is also not permissible to substitute acts of intent as to the participation of certain persons in a certain partnership or company with decisions of other entities that have no competence to make statements that would legally bind those certain (other) persons. Due to the statutory restriction on the freedom of legal action of the parties to the articles of association of a joint-stock company as well as of the general meeting of such company (laid down in Article 304 § 3 of the Code of Commercial Partnerships and Companies), it is not at all permissible to change the lower limit of the composition of the supervisory board of a joint-stock company. The term “consensual intention of parties’ encompasses the partnership’s or the company’s objects as defined in the partnership agreement or articles of association (see e.g. Article 21 § 1(2), Article 25(2), Article 91(2), Article 105(2), Article 130(2), Article 157 § 1(2) and Article 304 § 1(2) CCPC). Therefore, ’making contributions’ in a partnership or company, as defined in Article 3 CCPC is, of course, not a goal in itself, but only a means to achieve (implement) the common goal assumed by the partners or shareholders. The provisions relating to various statutory types of commercial partnerships and companies do not, in principle, directly specify a designated obligation of a member to additionally cooperate in a manner different than that described in Article 3 CCPC. However, such an obligation follows indirectly from legal provisions: a) in a general partnership, a limited partnership and limited joint-stock partnership - with regard to the obligation of a general partner to manage the affairs of the company, unless a given partner has been released from the obligation to manage such affairs; b) in a professional partnership - with regard to the partner’s exercise of his or her (liberal) profession within the partnership; c) in a limited partnership - with regard to the limited partner’s designation in the text of the agreement of a specified amount of liability towards the company’s creditors for the obligations of the company, i.e. the so-called ’limited partnership sum’. The partnership agreement or articles of association may impose obligations on a particular member of the partnership or company other than the payment of a contribution (cf., e.g., Article 159 or 304 § 2(2) CCPC). In such a case, the obligation to fulfil the thus designated duties arises from an additional contractual obligation of the concerned member and falls within the scope of that member’s duty of cooperation. Its object is that specifically designated (in the partnership agreement or in articles of association) duty to the company. If, after the registration of a commercial company, it turns out that its articles of association fail to identify the members or fail to specify share rights acquired by the shareholders, the registration court, acting pursuant to Article 21 of the Polish Code of Commercial Partnerships and Companies, may issue a decision on the dissolution of the company entered in the register on the grounds that ’no articles of association have been concluded’ - see Article 21 § 1(1) of CCPC. If, on the other hand, ’the articles of association do not contain provisions concerning the company’s name, the company’s objects, share capital or contributions’, the court will only be able to rule on the dissolution of such a company on the basis of Article 21(1)(2) of CCPC.